[Southeast side of University Union] - P. K. Phillips::::::photographer::: (1979)
The side of the Union facing South Perimeter Road, which has two light-blue Volkswagen Beetles and a yellow car parked on it. Some landscaping foliage surrounds the Union plaza and is further enclosed with a small, outside concrete wall to separate the Union from the street.